MEDIA PEMBELAJARAN BERBASIS GAME ANDROID PADA PEMBELAJARAN ANGKA DAN HURUF DI PAUD - Liza Trisnawati Trisnawati; Ira Puspita; Fitri Abdillah; Seri Hartati (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
In the current era of globalization, technology is very rapidly developing and widespread in various fields. We can see this from the many innovations that have emerged and developed at the same time, one of which is digital-based learning media. In the field of education, technology helps the learning process so as to produce educational media. Especially in the field of education, the learning process of students at this time is more emphasized on visual education that looks attractive with the addition of images and sounds. In general, the recognition of letters and number shapes is still carried out with a conventional system that is still less interesting. The purpose of this study is to help students to easily understand the material on letter recognition and number shapes in early childhood students. This research used the GDLC (Game Development Life Cycle) method and the creation of this application used Buildbox. The data collection is in the form of literature studies, interviews and observations. The letter recognition and number shape application was tested using black box testing successfully. This application can be learned anytime and anywhere using a Smartphone.